Intramolecular Radical Cyclization of Vinyl, Aryl and Alkyl Halides Using Catalytic Amount of Bis-tri-n-butyltin Oxide/Sodium Borohydride: A Novel Entry to Functionalized Carbocycles - Dinesh, Tarur Konikkaledom; Palani, Namasivayam; Balasubramanian, Sengottuvelan (Synlett, 2015)
We wish to report a facile method in which a catalytic amount of bis-tri-n-butyltinoxide (TBTO) in the presence of sodium borohydride efficiently brings about the intramolecular radical cyclization of a variety of vinyl, aryl and alkyl halides to their corresponding functionalized bicyclic and tricyclic carbocycle frameworks. The methodology obviates the need for stoichiometric amounts of tin reagent normally required for radical cyclization reactions.
Keywords: Barbier reaction; radical cyclization; allylic halide; bis-tri-n-butyltinoxide